2006
DOI: 10.1667/rr3564.1
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Translocation and DNA-Binding Activity of NFKB (NF-κB) after Exposure of Human Monocytes to Pulsed Ultra-wideband Electromagnetic Fields (1 kV/cm) Fails to Transactivate κB-Dependent Gene Expression

Abstract: The objective of this study was to investigate whether exposure of human monocytes to a pulsed ultra-wideband electromagnetic field (EMF) of 1 kV/cm average peak power triggers a signaling pathway responsible for the transcriptional regulation of NFKB (NF-kappaB)-dependent gene expression. Human Mono Mac 6 (MM6) cells were exposed intermittently to EMF pulses for a total of 90 min. The pulse width was 0.79+/-0.01 ns and the pulse repetition rate was 250 pps. The temperature of the medium was maintained at 37 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Leszczynski et al (2004), for example, observed an increase in HSP27 phosphorylation—which can be considered an antiapoptotic event (Morimoto 1998)—and a concomitant increase in stability of stress fibers of cells and down-regulation of genes of the Fas/TNF-α apoptotic pathway. Other authors did not observe simultaneous change in gene expression and in related downstream events: Natarajan et al (2006) reported increased DNA-binding activity of NF-kappaB in human monocytes but no transactivation of kappaB-dependent gene expression after exposure to pulsed ultra-wide-band electromagnetic fields. Nikolova et al (2005) observed changes in gene expression but without detectable change in cell physiology.…”
Section: Discussionmentioning
confidence: 93%
“…Leszczynski et al (2004), for example, observed an increase in HSP27 phosphorylation—which can be considered an antiapoptotic event (Morimoto 1998)—and a concomitant increase in stability of stress fibers of cells and down-regulation of genes of the Fas/TNF-α apoptotic pathway. Other authors did not observe simultaneous change in gene expression and in related downstream events: Natarajan et al (2006) reported increased DNA-binding activity of NF-kappaB in human monocytes but no transactivation of kappaB-dependent gene expression after exposure to pulsed ultra-wide-band electromagnetic fields. Nikolova et al (2005) observed changes in gene expression but without detectable change in cell physiology.…”
Section: Discussionmentioning
confidence: 93%
“…The cytokines IL-1b, IL-6, IL-10, and TNF-a were found unchanged in gene expression and protein production in LF EMF-exposed PBMCs [Pessina and Aldinucci, 1997;Ikeda et al, 2003] and rat and human lymphocytes [Jasti et al, 2001;Luceri et al, 2005]. NF-kB gene expression was also found unchanged in human monocytic cells in two separate studies [Miller et al, 1999;Natarajan et al, 2006]. Although the setup of the experimental and exposure conditions differed greatly from our study, most of these studies used a 50 Hz signal.…”
Section: Discussionmentioning
confidence: 99%
“…However, caspase-9 and Apaf-1 remain unchanged in another study [47]. The tumor necrosis fac- [63] tor (TNF)-inducible protein A20 and BCL2-related factor A1 are both upregulated [59]. In other studies, deathassociated protein DAP3 is upregulated [48], but another Dap is downregulated [51].…”
Section: (Ii) Stress Response Related Genes (Not Heat-shock Proteins)mentioning
confidence: 89%